The Evolution of Simulation-Based Learning Across the Disciplines, 1965–2018: A Science Map of the Literature. (February 2020) - Hallinger, Philip; Wang, Ray
Background. Simulation-based learning (SBL) has been applied and studied in educational settings for at least six decades. While numerous reviews of research have been conducted from different perspectives, none to date have used bibliometric methods to analyze the evolution of simulation-based learning as a 'knowledge base'. Aim. The review sought to document thegrowth and geographic distribution of research on SBL. In addition, the review aimed to identifykey authors and documents, and analyze theintellectual structure of this knowledge base. Finally, the review highlighted emerging topics in this literature. Method. The authors identified 2, 812 Scopus-indexed SBL documents published between 1965 and 2018. Bibliographic data were exported from Scopus and analyzed using VOSviewer software. Analyses included descriptive statistics, citation and co-citation analysis, and keyword co-occurrence analysis. Results. The review found a rapidly increasing publication trajectory with 90% of the literature published since 2000. Although SBL studies have been authored in 94 different countries, the literature is concentrated inAnglo-American-European societies. The review found that the intellectual structure of this knowledge base is comprised of fourschools of thought encompassing research on SBL in management education, medical education, technology-enhanced SBL, and learning theories in SBL. Another notable finding was that SBL researchers in medical and management education have progressed on parallel tracks leading to the balkanization on knowledge. Surprisingly, the conceptual core of the field is located in the school of thought associated with learning theories in SBL. This implies that SBL is a subfield of education rather than a discipline in and of itself. Emerging topics that have attracted scholars writing on SBL in recent years are identified and implications for future research discussed.